Pelaksanaan Pengelolaan Objek Wisata Mandala Suci Wenara Wana oleh Desa Adat Padangtegal, Kecamatan Ubud, Kabupaten Gianyar - Ni Komang Ayu Sri Widiari; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Preferensi Hukum, 2022)
Tourism objects can be regarded as natural resources, the results of their use resulting in an increase in the economy. The surrounding nature in Bali is used as an attractive tourist destination such as the Mandala Suci Wenara Wana tourist attraction which is managed directly independently by the Padangtegal Traditional Village. Management still looks a lot that is not in accordance with the procedures, seen in terms of environmental protection, there is still garbage disposal. For this reason, this study examines the implementation of the management of the Mandala Suci Wenara Wana tourism object, Padangtegal Traditional Village, Ubud District, Gianyar Regency and explains the implications of implementing the management of the Mandala Suci Wenara Wana tourist attraction which is managed by the Padangtegal Traditional Village, Ubud District, Gianyar Regency. This study was designed with empirical legal research with a sociology of law approach, the data sources used were two, namely primary and secondary legal materials. To obtain valid data, researchers collected data using observation, documentation, and interview techniques. The results of the study indicate that the implementation of the management of the Mandala Suci Wenara Wana Tourism object has not run optimally because there is a vacancy in the arrangement of the party who has the authority to carry out the management to date. The implications of managing the Mandala Suci Wenara Wana Tourism Object from an economic point of view are the use of land as a place of business, and enjoying free parking facilities in the tourist attraction area, but the comfort and safety of the people around the object are disturbed due to the presence of monkeys that often roam to people's homes.